Evaluasi Aplikasi Fungi Mikoriza Arbuskula (FMA) dan Respon Pertumbuhannya Terhadap Jati (Tectona grandis Linn. F.) di Persemaian - Jenny Rumondang; Yadi Setiadi (Jurnal Silvikultur Tropika, 2011)
Evaluation of Arbuscula Mycorrizhae Fungi (AMF) Application to Teak (Tectona grandis Linn. F.) Seedling and Its Growth Responses in NurseryTeak  (Tectona grandis Linn. F.) was one of Verbenaceae family that categorized into luxurious goods commodity. One of difficulties in meeting of teak woods demands was the growth of teak in the nursery that takes long enough time, thus need efforts to accelerate the growth and improve the quality of teak in the nursery. Arbuskula Mycorrizhae Fungi (AMF) was one of endomycorrizhae that could associate with teak. Mycorrizhae could provide phospor that has important role for (Adenosin Triphospate) ATP creation in the plant. The objective of this research was to collect and provide information from many performed research for evaluating and analyzing the effect of endomycorrizhae inoculation to teak seedling growth. Result of this evaluation about application AMF of teak seddling that  G. aggregatum dan  G.manihotis-3 could improve the growth of teak seddling. G. manihotis-3 was effective AMF that improve the growth of teak seedling. The addition of M-Dext on 10 cc/l and 30 cc/l doses, and 3 gr of NPK could support the improvement of teak seedling growth that inoculated with AMF. Used utilization of growing media from sterilized mixture of sand and soil could support the growth of teak seedling that inoculated with AMF in nursery. Inoculation technique with hole-system or layering system could used to application teak seedling with AMF in nursery.